Determinants of Anemia Among Children Aged 6 to 59 Months in Dilla Town, Southern Ethiopia: A Facility Based Case Control Study - Muluken Jembere MPH; Robel Hussen Kabthymer MSc; Amare Deribew PhD (SAGE Publishing, 2020)
Background. Globally, anemia is a widespread public health problem associated with increased risk of morbidity and mortality. Under 5 children have greater risk of anemia. The level of burden and the risk factors for anemia vary in different settings. Identifying local factors will have important implications for health intervention programs aimed to tackle the burden. Our study aims to investigate the determinants of anemia among under 5 children in the study area. Methods. Facility based unmatched case control study was conducted among 413 (137 cases and 276 controls) children of Dilla town. Cases were children who had hemoglobin level of less than 11 g/dl and controls were children aged 6 to 59 months with hemoglobin ≥11 g/dl. Quota and simple random sampling was used for cases and controls respectively. Data on socio-demographic, dietary diversity score, food security, anthropometry, hemoglobin level, malaria infection and intestinal parasites were collected. Data were analyzed with SPSS version 25. Bi-variate and multivariate binary logistic regression analysis was used to identify independent determinants of anemia. P -value less than .05 were used to declare statistical significance. Result. In the multivariate analysis, having more than 1 under 5 children in the households (AOR = 3.03, 95%CI = 1.35-6.81), intestinal parasitosis (AOR = 4.42, 95%CI = 2.07-9.44), food insecurity (AOR = 2.75, 95% CI = 1.39-5.45), and stunting (AOR = 6.09, 95% CI = 2.53-14.67) were determinants of anemia among children aged 6 to 59 months. Conclusion. Some of the identified factors are modifiable that could be targeted to reduce childhood anemia. Family planning education, provision of anti-helminthic drugs and ensuring household food security will be beneficial to tackle anemia.